Predicting the Unseen: Entrepreneurial Opportunity on Entrepreneurial Intention - Kusumawijaya, Ida Ketut (International Review of Management and Marketing, 2019)
This study examines entrepreneurial opportunity to predict entrepreneurial intention of star hotels emloyee in Bali. Respondents of this study were star hotels employees in Bali total 156 people with 100% response rate. The initial evaluation was carried out by evaluating the measurement model, namely the validity and reliability of each reflective construct. Next is the evaluation of the structural model for testing the research model where each research instrument uses a 5 Likert scale measurement, with the WarpPLS 4.0 program. The parameters significance is determined by resampling bootstrapping and using 500 sub-samples of equal size to that of the original sample. The results and discussion show that the hypothesis testing showing innovation and growth of star hotel employees in Bali are able to predict entrepreneurial intention not significantly. Financial return can predict employee star hotels in Bali significantly entrepreneurial intention. The investment return of star hotel employees in Bali can predict significant entrepreneurial intention. The hypothesis testing indicates that the internal factor is able to predict entrepreneurial intention the star hotel employee in Bali significantly. And this research indicates that the customer predicts entrepreneurial intention star hotel employee in Bali not significantly. keywords: entrepreneurial intention, innovation and growth, financial return, investment return, internal factor JEL Classifications: L26, M21 DOI: https://doi.org/10.32479/irmm.8662